ANALYSIS OF PERFORMANCE AND CONNECTION COSTS ON THE NGEMPLAK SIMONGAN ROAD SECTION - saifudin, ananda lukman; Suwandi, Putri Anggi Permata; Yudaningrum, Farida (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2023)
Abstract. Traffic congestion is caused by an imbalance between the increase in vehicle ownership and the growth of available road infrastructure and the effective capacity of existing road sections is smaller than the planned road capacity due to roadside obstacles.The phenomenon of traffic jams is an interesting thing to study, as is the traffic jam caused by the influence of factory activities on Jalan Ngemplak Simongan. This can result in obstruction of traffic flow and reduced levels of road service so that road users who only pass through this place receive negative impacts in the form of longer travel times which ultimately lead to external costs in the form of additional vehicle operational costs (BOK).Key words: factors causing congestion, road performance, congestion costs